Political Economy of Nigeria-Benin Republic Bilateral Relations - Nwokedi, Michael E.; Obasi, Christopher U. (University of Nigeria Journal of Political Economy, 2025)
At the dawn of the 21st Century, the Nigerian economy is in dire straits. The Country’s frantic search for development underscores the need for a constant review of diplomatic, economic and defence/security relations with next door neighbours, with a view to harnessing such relations for development. Given her proximity to Nigeria, the Republic of Benin is considered critical to Nigeria’s development especially in terms of Nigeria’s anti-smuggling crusade which comes as part of efforts to revive the Nigerian economy; with attendant implications for national security. The Republic of Benin also seeks to maximize the benefits of diplomatic relations with Nigeria, in view of the latter’s status as the largest economy in West Africa. However, there are fears that Nigeria has not maximized the benefits of her relations with Benin Republic. Worse still, it appears that the Republic of Benin is leveraging Nigeria’s diplomatic gaffes to advance her economic interests. Accordingly, this paper explores the trajectory of diplomatic, economic and defence/security relations between Nigeria and Benin Republic. Applying the Interdependence Theory, it exposes the lopsidedness of economic benefits in Nigeria-Benin Republic relations and makes recommendations in the interest of Nigeria. Data collation was qualitative while research design is exploratory.